Using a Heliospheric Upwinding eXtrapolation Technique to Magnetically Connect Different Regions of the Heliosphere - Riley, Pete; Issan, Opal (Frontiers in Physics, 2021)
Understanding how coronal structure propagates and evolves from the Sun and into the heliosphere has been thoroughly explored using sophisticated MHD models. From these, we have a reasonably good working understanding of the dynamical processes that shape the formation and evolution of stream interaction regions and rarefactions, including their locations, orientations, and structure. However, given the technical expertise required to produce, maintain, and run global MHD models, their use has been relatively restricted. In this study, we refine a simple Heliospheric eXtrapolation Technique (HUX) to include not only forward mapping from the Sun to 1 AU (or elsewhere), but backward mapping towards the Sun. We demonstrate that this technique can provide substantially more accurate mappings than the standard, and often applied "ballistic" approximation. We also use machine learning (ML) methods to explore whether the HUX approximation to the momentum equation can be refined without loss of simplicity, finding that it likely provides the optimum balance. We suggest that HUX can be used, in conjunction with coronal models (PFSS or MHD) to more accurately connect measurements made at 1 AU, Stereo-A, Parker Solar Probe, and Solar Orbiter with their solar sources. In particular, the HUX technique: (1) provides a substantial improvement over the "ballistic" approximation for connecting to the source longitude of streams; (2) is almost as accurate, but considerably easier to implement than MHD models; and (3) can be applied as a general tool to magnetically connect different regions of the inner heliosphere together, as well as providing a simple 3-D reconstruction.